Political Participation in Nigerian Democracy: An Examination Of A Few Chosen Local Government Areas in Ondo State During The 2015 General Elections in Nigeria: Voter Apathy and the Electoral Process. - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (Green Social: International Journal of Law and Civil Affairs, 2025)
This study examines the level of political participation among the populace and highlights the importance of elections as a key component of a democratic system. Scholars widely acknowledge that involvement in electoral processes serves as a primary indicator of how well a country has embraced the principle of social equality within the international framework. The study employed a mixed-method approach, utilizing both qualitative and quantitative techniques. The quantitative instrument used was the Political Participation Attitude Scale (PPAS), while qualitative data were collected through the Focus Group Guide on Political Participation (FGGPP). The research posed and addressed three core research questions. The findings reveal that 57% of respondents did not actively participate in political activities. Gender was found to influence levels of engagement; 30% of male respondents and 13% of female respondents reported active involvement in political activities, while 38% of males and 12% of females consistently participated in voting. Furthermore, the survey indicated that a majority of respondents (53%) lacked trust in their political leaders. Based on these findings, the study recommends that Nigeria urgently adopt both formal and informal political education strategies to enhance civic awareness and participation. Additionally, the Independent National Electoral Commission (INEC) is encouraged to develop mechanisms that will ensure broader voter turnout in the upcoming 2015 general elections.